2023
DOI: 10.1002/ueg2.12424
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported treatment effectiveness for Crohn's disease using a novel crowdsourcing web‐based platform

Abstract: Background and AimsInternet and social media platforms have become an unprecedented source for sharing self‐experience, potentially allowing the collection and integration of health data with patient experience. StuffThatWorks (STW) is an online open platform that applies machine learning and the power of crowdsourcing, where patients with chronic medical conditions can self‐report and compare their individual outcomes using a structured online questionnaire. We aimed to conduct a cross‐sectional, internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In this issue, Engel et al provide new and useful information about how these resources can be applied for research. 15 Here, StuffThatWorks (www.stuffthatworks.health), a platform designed to collect clinical information from chronic conditions using a machine learning algorithm, was used to gather patient experience on different medical treatments for CD. The authors showed that anti-TNF agents were ranked as the most effective by patients, followed by ustekinumab and vedolizumab, respectively.…”
Section: Surfing the Web As A Patient With Ibd: New Horizonsmentioning
confidence: 99%
“…In this issue, Engel et al provide new and useful information about how these resources can be applied for research. 15 Here, StuffThatWorks (www.stuffthatworks.health), a platform designed to collect clinical information from chronic conditions using a machine learning algorithm, was used to gather patient experience on different medical treatments for CD. The authors showed that anti-TNF agents were ranked as the most effective by patients, followed by ustekinumab and vedolizumab, respectively.…”
Section: Surfing the Web As A Patient With Ibd: New Horizonsmentioning
confidence: 99%
“…For all gastroenterology, all the way to use AI tools such as ChatGPT or SciScope, we need to evaluate these tools in patient care. 10 Implementation where and when helpful and clear guidelines are pivotal and ideally published in our journal.…”
mentioning
confidence: 99%